A BIBLIOMETRIC ANALYSIS OF ENGINEERING EDUCATION IN THE METAVERSE - Veselina Nedeva; Snejana Dineva; Svetoslav Atanasov (Інформаційні технології і засоби навчання)
The Metaverse is a persistent and shared digital environment that blends physical and virtual reality, allowing for advanced multisensory interactions. Its acceptance has grown significantly since the COVID-19 pandemic. Nevertheless, despite its potential benefits for education, there are notable gaps in assessing learning processes within the Metaverse, especially concerning legal limitations and government oversight. This study aims to enhance the educational experience by promoting innovative, interactive, and engaging learning environments in various engineering disciplines, thereby equipping students with the skills necessary for success in a rapidly evolving technological landscape.This paper investigates the use of the Metaverse in engineering education through bibliometric analysis to identify key trends, challenges, and opportunities. By employing advanced tools like Publish or Perish and VOSviewer, the study analyzes bibliographic networks and statistical data to map the scholarly landscape and impact of this technology. The bibliometric analysis offers quantitative insights into research trends, citation counts, and author influence, which are presented in tables and charts for better visualization. This paper aim to enhance our understanding of how digital and immersive technologies are reshaping educational practices and boosting student engagement, motivation, and outcomes. The analysis underscores the importance of ongoing research and investment in the Metaverse as a vital resource for contemporary education, especially in engineering disciplines that thrive on interactive and hands-on learning environments. This research, despite certain limitations, lays important groundwork for understanding how the Metaverse can transform engineering education. By thoroughly analyzing and delineating the current landscape, it seeks to provide valuable insights that will guide future investigations and practical applications.